Linking axionlike dark matter to neutrino masses - Carvajal, C. D.R.; Sánchez-Vega, B. L. [UNESP]; Zapata, O. (American Physical Society (APS), 2017)
We present a framework linking axionlike particles (ALPs) to neutrino masses through the minimal inverse seesaw (ISS) mechanism in order to explain the dark matter (DM) puzzle. Specifically, we explore three minimal ISS cases where mass scales are generated through gravity-induced operators involving a scalar field hosting ALPs. In all of these cases, we find gravity-stable models that provide the observed DM relic density and, simultaneously, are consistent with the phenomenology of neutrinos and ALPs. Remarkably, in one of the ISS cases, the DM can be made of ALPs and sterile neutrinos. Furthermore, other considered ISS cases have ALPs with parameters that are within the reach of proposed ALP experiments.